Intracranial Hemorrhages in Neonates: Incidence, Risk Factors, and Treatment - Andersson, Nadine G.; Kenet, Gili (Seminars in Thrombosis and Hemostasis, 2022)
Hemostasis is a dynamic process that starts in utero. Neonates, especially those who are born preterm, are at high risk of bleeding. The coagulation system evolves with age, and the decreased levels of coagulation factors along with hypo-reactive platelets are counterbalanced with increased activity of von Willebrand factor, high hematocrit and mean corpuscular volume as well as low levels of coagulation inhibitors that promote hemostasis. Neonates with congenital bleeding disorders such as hemophilia are at even higher risk of bleeding complications. This review will focus upon one of the most devastating complications associated with neonatal bleeding: intracranial hemorrhages (ICH). While etiology may be multifactorial and impacted by maternal as well as fetal risk factors, the mode of delivery certainly plays an important role in the pathogenesis of ICH. We will address prematurity and congenital bleeding disorders such as hemophilia A and B and other rare bleeding disorders as risk factors and present an updated approach for treatment and possible prevention.
Keywords: intracranial hemorrhage; neonates; bleeding disorders